Contract negotiation and the coase conjecture: A strategic foundation for renegotiation-proof contracts - Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2015)
What does contract negotiation look like when some parties hold private information and negotiation frictions are negligible? This paper analyzes the above question and provides a foundation for renegotiation-proof contracts in a related environment. The model extends the framework of the Coase conjecture to situations in which the quantity or quality of the good is endogenously determined and to more general environments in which the traded goods are complements or substitutes. All equilibria converge to a unique outcome as frictions become negligible, which is separating, efficient, and straightforward to characterize.
Keywords: 330